2017
DOI: 10.3141/2631-03
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticplastic–Fracture Modeling of Asphalt Mixtures Under Monotonic and Repeated Loads

Abstract: Rutting and cracking occur simultaneously in asphalt mixtures as observed in the field and laboratory. Existing mechanical models have not properly addressed viscoelastic and viscoplastic deformation together with cracking due to model deficiencies, parameter calibration and numerical inefficiency. This study develops viscoelastic-plastic-fracture (VEPF) models characterizing viscoelasticity (VE) by Prony model and viscoplasticity (VP) by Perzyna's flow rule with a Generalized Drucker-Prager (GD-P) yield surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The viscoplastic and viscofracture properties of the asphalt concrete have also been coupled in the viscoelastic constitutive models based on the weak-form PDE based FE method (26). It demonstrates that accurate viscoelastic and viscoplastic responses can be modeled and predicted for the asphalt concrete.…”
Section: Finite Element Modeling Of Ugb In Flexible Pavements Weak Fomentioning
confidence: 98%
See 2 more Smart Citations
“…The viscoplastic and viscofracture properties of the asphalt concrete have also been coupled in the viscoelastic constitutive models based on the weak-form PDE based FE method (26). It demonstrates that accurate viscoelastic and viscoplastic responses can be modeled and predicted for the asphalt concrete.…”
Section: Finite Element Modeling Of Ugb In Flexible Pavements Weak Fomentioning
confidence: 98%
“…The viscoelastic constitutions of asphalt concrete have been successfully modeled using a weak-form partial differential equation (PDE)-based FEM technique in COMSOL Multiphysics program ( 22 ). The viscoplastic and viscofracture properties of the asphalt concrete have also been coupled in the viscoelastic constitutive models based on the weak-form PDE based FEM method ( 26 ). It demonstrates that accurate viscoelastic and viscoplastic responses can be modeled and predicted for the asphalt concrete.…”
Section: Finite Element Modeling Of Ugb In Flexible Pavementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective stress has been successfully applied in the damage characterization of asphalt mixtures under different loading modes 25,26 . The relations between apparent and effective stresses and strains are presented in Equations 1 and 2, 27 boldσ=()1ξtrueσ˜ trueε˜=()1ξboldε where boldσ and boldε are the apparent stress and strain tensors; trueσ˜ and trueε˜ are the effective stress and strain tensors; ξ is the damage density.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…As Equation 7, the stress–strain relation of viscoelastic materials can be expressed as Equation 18. {τnkdεkkn,italicdashpotdtgoodbreak−εkkTotalgoodbreak+εkkn,italicdashpotgoodbreak=0τnμitalicdeitalicijn,dashpotdtgoodbreak−eijTotalgoodbreak+eijn,italicdashpotgoodbreak=0 lefttrueσitalicijitalicTotalt=kεitalickkitalicTotalδitalicij+2μeitalicijitalicTotal+false∑n=1NleftknεitalickkitalicTotalεitalickkn,dashpotδitalicij+2μneitalicijitalicTotaleitalicijn,dashpot By introducing the damage density and apparent stress and strain tensors, the final form of the stress–strain relation of viscoelastic materials in this study is shown in Equation 19, 27 lefttrueσitalicijA,Totalt=()1goodbreak−ξ2kεitalickkA<...>…”
Section: Theoretical Modelsmentioning
confidence: 99%